Comparison of Adopted and Nonadopted Individuals Reveals Gene–Environment Interplay for Education in the UK Biobank. (May 2020) - Cheesman, Rosa; Hunjan, Avina; Coleman, Jonathan R. I.; Ahmadzadeh, Yasmin; Plomin, Robert; McAdams, Tom A.; Eley, Thalia C.; Breen, Gerome
Polygenic scores now explain approximately 10% of the variation in educational attainment. However, they capture not only genetic propensity but also information about the family environment. This is because of passive gene–environment correlation, whereby the correlation between offspring and parent genotypes results in an association between offspring genotypes and the rearing environment. We measured passive gene–environment correlation using information on 6, 311 adoptees in the UK Biobank. Adoptees' genotypes were less correlated with their rearing environments because they did not share genes with their adoptive parents. We found that polygenic scores were twice as predictive of years of education in nonadopted individuals compared with adoptees ( R 2 s = .074 vs. .037, p = 8.23 × 10 −24 ). Individuals in the lowest decile of polygenic scores for education attained significantly more education if they were adopted, possibly because of educationally supportive adoptive environments. Overall, these results suggest that genetic influences on education are mediated via the home environment.